The Instability Severity Index Score Revisited: Evaluation of 217 Consecutive Cases of Recurrent Anterior Shoulder Instability. Issue 7 (29th July 2019) - Provencher, Matthew T.; Sanchez, George; Bernhardson, Andrew S.; Peebles, Liam A.; Haber, Daniel B.; Murphy, Colin P.; Sanchez, Anthony
Objectives: The instability severity index score (ISIS) was designed to predict the risk of recurrence after arthroscopic instability shoulder surgery and to better predict those who would benefit from an open or bone transfer operation. Although this score has been widely disseminated to predict recurrence, there are certain areas in which preoperative assessment is limited, especially in radiographic workup. The objective of this study was to examine the validity of ISIS based on its existing variables, as well as to evaluate additional imaging and patient history variables pertinent to the potential redevelopment of a new score to assess risk of recurrent anterior instability following an arthroscopic Bankart repair. Methods: All consecutive patients were prospectively enrolled with recurrent anterior shoulder instability who subsequently underwent an arthroscopic stabilization with minimum 24 months follow-up. Exclusion criteria included, prior surgery on the shoulder, posterior or multidirectional instability, or a rotator cuff tear. All instability severity index score variables were recorded (age <20, degree and sport type, hyperlaxity, Hill Sachs on AP xray, glenoid loss of contour on AP xray), as well as additional variables: 1. Position of arm at dislocation; 2. Number of instability events; 3. Total time of instability; 4. Glenoid bone loss percent; 5. Amount of attritional glenoid bone loss; 6. Hill Sachs measures (H/W/D and volume), and outcomes (recurrent instability) and scores (WOSI, ASES and SANE). Regression analysis was utilized to determine preoperative variables that predicted outcomes and failures. Results: There were 217 consecutive patients (209 male-96.5%, 8 female-3.5%) who met criteria and were all treated with a primary arthroscopic shoulder stabilization during a 3.5-year period (2007-2011), with mean follow-up of 42 (range, 26-58 mos). The mean age at first instability event was 23.9 (range, 16-48), with 55% right shoulder affected, 60% dominant shoulder. Outcomes were improved from mean scores preoperative (WOSI=1050/2100, ASES=61.0, SANE=52.5) to postoperative (WOSI=305/2100, ASES=93.5, SANE=95.5), and 11.5% (25/217) had evidence or recurrent instability or subluxation. A total of 51/217 were 20 years or under, hyperlaxity in 5, Hill Sachs on internal rotation XR in 77, glenoid contour on AP XR in 41, with an overall mean ISIS score of 3.6. Factors associated with failure were glenoid bone loss greater than 14.5%(p<0.001), total time of instability symptoms >11.5 months(p<0.03), Hill Sachs volume > 1.3 cm3 with H>1.5 cm, W>1.0 cm and D>5 mm(p<0.01), contact sport (p<0.01) and age 20 or under (p<0.01). There was no correlation in outcomes with Hill Sachs on IR or glenoid contour on XR (p>0.45), sports participation, and Instability Severity Score (mean=3.4 success, vs 3.9 failure, p>0.44). Conclusion: At nearly four years of follow-up, there was an 11.5% failure rate of scope stabilization surgery. However, there was no correlation between treatment outcome and the ISIS measure given a mean score of 3.4 with little difference identified in those that failed. However, several important parameters previously unidentified were detected including, glenoid bone loss >14.5%, Hill Sachs volume >1.3 cm3, and time length of instability symptoms. Therefore, the ISIS measure may need to be redesigned in order to incorporate variables that more accurately portray the actual risk of failure following arthroscopic stabilization.